2018
DOI: 10.1242/dmm.035147
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sex hormones, the vaginal microbiome and immunity in HIV-1 susceptibility in women

Abstract: The role of sex hormones in regulating immune responses in the female genital tract has been recognized for decades. More recently, it has become increasingly clear that sex hormones regulate susceptibility to sexually transmitted infections through direct and indirect mechanisms involving inflammation and immune responses. The reproductive cycle can influence simian/human immunodeficiency virus (SHIV) infections in primates and HIV-1 infection in ex vivo cervical tissues from women. Exogenous hormones, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 185 publications
(273 reference statements)
1
57
0
1
Order By: Relevance
“…In a similar vein, studies have shown that women with bladder issues such as urge urinary incontinence have more diverse bladder microbiomes than women without incontinence (69,70). Additionally, studies have shown that women with imbalances in Lactobacillus in their vaginal microbiome can have changes in hormones associated with cervicovaginal inflammation, which leads to changes in their vaginal immunity and HIV susceptibility (10,57,71). It is possible that the handling and stress of the study contributed to an increase in the microbiome diversity for Control animals, and that the three Treatment rats with lower rate of increase or a decrease were affected by stimulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a similar vein, studies have shown that women with bladder issues such as urge urinary incontinence have more diverse bladder microbiomes than women without incontinence (69,70). Additionally, studies have shown that women with imbalances in Lactobacillus in their vaginal microbiome can have changes in hormones associated with cervicovaginal inflammation, which leads to changes in their vaginal immunity and HIV susceptibility (10,57,71). It is possible that the handling and stress of the study contributed to an increase in the microbiome diversity for Control animals, and that the three Treatment rats with lower rate of increase or a decrease were affected by stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…This reduction of a dominating species and overall increase in the diversity of the vaginal microbiome is associated with an overall reduction in vaginal health in postmenopausal women (8). Postmenopausal women are 7.8 times more likely to have a more diverse vaginal microbiome than are premenopausal women (9), and this may be due to decreases in their concentrations of ovarian hormones (10). This suggests that hormone changes associated with menopause may have an effect on the vaginal microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by our finding that the observed changes in bacterial vaginal diversity in the rhesus monkeys coincide with changes in the pH, a functional measurement of the vaginal ecosystem. Understanding the causal relationships that regulate and control changes in vaginal ecosystem is a current challenge for both NHP and human microbiome studies (reviewed by ( 22 )) and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, estradiol has been implicated in the shift from a Lactobacillus-poor to a Lactobacillus-rich vaginal microbiota during puberty, as well as a reverse shift after menopause (86). Estrogen-induced glycogen synthesis in epithelial cells and production of glycogen-metabolites (maltose, maltotriose, α-dextrines) provides substrates for conversion to lactic acid by Lactobacilli (87)(88)(89). At reproductive age, a healthy vaginal microbiota was found to amplify the fluctuation in local immune responses in synchrony with hormonal changes during the menstrual cycle (90).…”
Section: Hormonal Regulation Of Host-vaginal Microbiota Interactionsmentioning
confidence: 99%